Letters to the sons of society : a father's invitation to love, honesty, and freedom - Senghor, Shaka (Convergent, 2022)
"The New York Times bestselling author of Writing My Wrongs invites men everywhere on a journey of honesty and healing through this book of moving letters to his sons-one whom he is raising and the other whose childhood took place during Senghor's nineteen-year incarceration. Shaka Senghor has lived the life of two fathers. With his first son, Jay, born shortly after Senghor was incarcerated for second-degree murder, he experienced the regret of his own mistakes and the disconnection caused by a society that sees Black lives as disposable. With his second, Sekou, born after Senghor's release, he has experienced healing, transformation, intimacy, and the possibilities of a world where men and boys can openly show one another affection, support, and love. In this collection of beautifully written letters to Jay and Sekou, Senghor traces his journey as a Black man in America and unpacks the toxic and misguided messages about masculinity, mental health, love, and success that boys learn from an early age. He issues a passionate call to all fathers and sons-fathers who don't know how to show their sons love, sons who are navigating a fatherless world, boys who have been forced to grow up before their time-to cultivate positive relationships with other men, seek healing, tend to mental health, grow from pain, and rewrite the story that has been told about them. Letters to the Sons of Society is a soulful examination of the bond between father and sons, and a touchstone for anyone seeking a kinder, more just world"--